From Tradition to Transformation: Addressing Challenges and Trends in Arabic Syntax Mastery via Problem-Based Learning - Faida Masruroh; Abdul Basith (Lughawiyyat)
Understanding and mastering Arabic syntax have a significant contribution to comprehending religious sciences, especially the books that use the Arabic language. The teaching method used can influence the enthusiasm, motivation, and outcomes of student learning. The purpose of this research is to determine the effectiveness of the problem-based learning method in improving understanding and mastery of Arabic syntax. In this study, data were collected using a quasi-experimental methodology to analyze it quantitatively, determining the effectiveness of using PBL in Arabic language acquisition for understanding grammar. We analyzed the quantitative data using independent sample t-test statistics. Using the independent sample t-test criteria, a Sig. (2-tailed) value < 0.05 indicates a significant result. The data testing produced a Sig. (2-tailed) value of 0.007, which is less than 0.05. This indicates that the intervention produced significant results. The problem-based learning method is very capable and effective in enhancing knowledge and understanding of Arabic syntax.